Self-care practice of patients with arterial hypertension in primary health care - Cláudia Rayanna Silva Mendes; Maira Di Ciero Miranda; Francisca Elisângela Teixeira Lima; Eva Anny Wélly de Souza Brito; Igor de Freitas; Érica Oliveira Matias (Rev Rene)
Objective: to evaluate the practice of self-care performed by patients with systemic arterial hypertension inprimary health care. Methods: this is a descriptive and cross-sectional study, conducted with 92 individualswith arterial hypertension in a primary care unit. The data collection occurred through script and data analyzedusing descriptive statistics (frequency, mean and standard deviation) and through the understanding of theadaption between capacity and self-care demand. Results: it was identified as a practice of self-care: adequatewater intake, salt intake and restricted coffee, satisfactory sleep period, abstinence from smoking and alcoholism,continuing pharmacological treatment and attending medical appointments. As the demands: inadequatefeeding, sedentary lifestyle, had no leisure activities, self-reported stress, and limited knowledge. Conclusion: although patients performed treatment a few years ago, still showed up self-care deficits, highlighting the needfor nurses to advise and sensitize about the importance of self-care practice.